Pendampingan Pembuatan Bahan Ajar Berbasis Kurikulum 2013 Bagi Guru Administrasi Perkantoran - Nikmah, Choirul; Pahlevi, Triesninda; Puspasari, Durinda; Puspasari, Durinta; Susilowibowo, Joni (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2018)
Changing of Curriculum involves change of substance, implementation, and evaluation. Teacher must have better preparation to improve learning quality. Around 73% of school in Jombang, from elementary to high school, had applied curriculum of 2013. However, teacher faces difficulty to prepare teaching material since there are several new subjects that never been taught previously in Vocational High School for office administration department. Besides, there are many books based on curriculum of 2013 are not sold freely. Thus, to solve those problems, teacher training and mentoring to create teaching material based curriculum 2013 needs to be held. It uses training and mentoring method. The training aims to enhance teacher competency to create teaching material, in the form of module, based on curriculum of 2013. The training result is module based on curriculum of 2013.